Effects of cobalt on mechanical properties of high silicon ductile irons. Issue 12 (12th August 2020) - González-Martínez, R.; Sertucha, J.; Lacaze, Jacques
Abstract : High silicon ductile irons are being developed due to their advantages relating to pearlitic-ferritic grades (high ductility, fully ferritic structures, good machinability, etc.). Recent studies reported that silicon contents higher than 5.2 wt-% originates drastic embrittlement due to chemical ordering. For improving the mechanical properties, the addition of other alloying elements becomes an interesting way of work. This study focuses on the cobalt effect on as-cast microstructures and mechanical properties of ductile irons with silicon contents that maximise ultimate tensile strength. The results obtained show that addition of 4 wt-% cobalt increases the ultimate tensile strength by about 10% and decreases the silicon content at the maximum in this property respecting the unalloyed alloys because cobalt enhances ordering as does silicon.